UNLOCKING THE POWER OF HALAL BRANDING: THE INFLUENCE OF BRAND IMAGE, TRUST, AND LOYALTY ON PURCHASE INTENTION OF WARDAH PRODUCTS - Sukmawati; Larasati Ayu Sekarsari (Al Tijarah, 2024)
Porpuse: This study aims to determine the effect of Brand Image, Brand Trust, and Brand Loyalty on Purchase Intention of wardah products. By using quantitative research with hypothesis testing, this study involved a sample of 156 respondents who used wardah skin care products. The analysis methods used include multiple linear regression. multiple linear regression, coefficient of determination (R2), coefficient of correlation and determination, t test, F test, and classical assumption test. using WarpPLS 7.0 software. Primary data for research was obtained through questionnaires. The results of this study indicate that Brand Image, Brand Trust, and Brand Loyalty have a significant effect on the Purchase Intention of Wardah skin care products. Wardah skin care products. In addition, brand image also has a considerable role in influencing the purchase intention of Wardah skin care products. However, perceived quality does not have a significant influence on the purchase intention of Wardah skincare products. Wardah skincare products.